Taking the pulse of the real economy using financial statement analysis: the european perspective - Lechien, Grégory (2018)
This article shows that an analysis of aggregated changes in profitability and profitability drivers is useful to forecast European economic growth. Furthermore the predictive power contained in profitability ratios is incremental and thus complementary to that contained in stock returns. Although European professional forecasters tend to incorporate equity returns and accounting information in their revisions of output growth expectations, their prediction errors can be anticipated based on aggregate changes in Return on Equity, Net Profit Margin and on stock returns. It implies that macro experts do not fully rely on easily available information to forecast E.U real GDP growth.